Extracting quantitative genetic interaction phenotypes from matrix combinatorial RNAi - Axelsson-Ekker, Elin; Sandmann, Thomas; Horn, Thomas; Boutros, Michael; Huber, Wolfgang; Fischer, Bernd (BMC bioinformatics, 2011)
Systematic measurement of genetic interactions by combinatorial RNAi (co-RNAi) is a powerful tool for mapping functional modules and discovering components. It also provides insights into the role of epistasis on the way from genotype to phenotype. The interpretation of co-RNAi data requires computational and statistical analysis in order to detect interactions reliably and sensitively.